Unsettled Heritage : Living next to Poland's Material Jewish Traces after the Holocaust - Weizman, Yechiel, 1982- (Book collections on Project MUSE., 2022)
"The book examines the fate and symbolic status of Jewish cemeteries and synagogues in post-WWII Poland, focusing on the ways in which these sites were perceived, discussed, and experienced by municipal officials and local inhabitants in small towns that had a substantial Jewish presence until the Holocaust"--